Possible mechanisms of the antifungal activity of fluconazole in combination with terbinafine against Candida albicans. (December 2014) - Khodavandi, Alireza; Alizadeh, Fahimeh; Vanda, Nasim Aghai; Karimi, Golgis; Chong, Pei Pei
Abstract Context: Candidiasis is a term describing infections by yeasts from the genus Candida, the majority Candida albicans. Treatment of such infections often requires antifungals such as the azoles, but increased use of these drugs has led to selection of yeasts with increased resistance to these drugs. Objective: Combination therapy would be one of the best strategies for the treatment of candidiasis due to increased resistance to azoles. Materials and methods: The antifungal activities of fluconazole and terbinafine were evaluated in vitro alone and in combination using broth microdilution test and time kill study. Eventually the expression level of selected genes involved in ergosterol biosynthesis of Candida was evaluated using semi-quantitative RT-PCR. Results: The obtained results showed the significant MICs ranging from 0.25 to 8 µg/mL followed by FICs ranged from 0.37 to 1 in combination with fluconazole/terbinafine. Our findings have demonstrated that the combination of fluconazole and terbinafine could also significantly reduce the expression of ERG1, 3, and 11 in the cell membrane of Candida in all concentrations tested ranging from 1.73- to 6.99-fold. Discussion and conclusion: This study was undertaken with the ultimate goal of finding the probable targets of fluconazole/terbinafine in C. albicans by looking at its effects on cell membrane synthesis.